Fabrication and Characterization of Isotropic and Anisotropic Magnetorheological Elastomers, Based on Silicone Rubber and Carbonyl Iron Microparticles - Puente Córdova, Jesús Gabino; Reyes Melo, Martín Édgar; Palacios Pineda, Luis; Martínez Perales, Imperio; Martínez Romero, Oscar; Elías Zúñiga, Alex (2018)
This article focuses on studying the rheological behavior of isotropic and anisotropic magnetorheological elastomers (MREs), made of carbonyl iron microparticles dispersed into a silicone–rubber matrix by considering 20 and 30 wt % of microparticles. Sample sets were prepared for each composition, with and without the application of an external magnetic ﬁeld. Experimental measurements of the material rheology behavior were carried out by a shear oscillatory rheometer at constant temperature, to determine both the shear storage modulus (G0) and shear loss modulus (G00) forallcharacterizedsamples. Then,experimentaldatacollectedfromtheisotropicandtheanisotropic material samples were used to plot the Cole-Cole diagrams to quantify the interfacial adhesion between carbonyl iron microparticles and the silicone-rubber matrix. Furthermore, the Fractional Zener Model (FZM) with two spring-pots in series is used for quantitative analysis of collected experimental data.